Disaster Recovery as a Cloud Service (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Within the modern advanced time, the danger of disasters—both normal and man-made—poses noteworthy dangers to organizational information judgment and operational progression. A novel concept called Catastrophe Recuperation as a Cloud Benefit (DRaaS) employments cloud computing to supply calamity recuperation arrangements that are reasonable and versatile. This consider analyzes the center thoughts of DRaaS, surveys the body of investigate and observational prove, and looks into the troubles and real-world employments of the innovation. The consider assesses the adequacy of DRaaS arrangements and looks at organizational appropriation patterns employing a mixed-method approach. Although it seems that DRaaS essentially reduces costs and speeds up recovery, problems with security, integration, and compliance persist. The primary focus areas of the proposals are future bearing research and the best practices for a successful DRaaS installation. The increasing dependence on digital infrastructure has heightened the need for efficient disaster recovery (DR) methods. Disaster Recovery as a Cloud Service (DRaaS) is researched here as an elastic, cost-saving substitute for conventional DR solutions. It is aimed at investigating how DRaaS can help industries reduce downtime and data loss, with a particular emphasis on small and medium-sized businesses (SMEs). The research utilizes a mixed-methods design, integrating comparative evaluation of cloud-based and on-premises DR models alongside case studies of organizations using DRaaS. Recovery time objective (RTO), recovery point objective (RPO), cost-effectiveness, and system robustness are measured through simulation and user-reported values. Outcomes show that DRaaS decreases RTO and RPO dramatically when compared to traditional systems, while providing increased flexibility and less capital investment. SMEs especially enjoy the pay-as-you-go approach and automated failover options. Concerns regarding data sovereignty and vendor lock-in are still significant challenges. Finally, DRaaS appears to be an efficient and feasible solution for disaster recovery in the contemporary era, particularly for companies requiring agility and cost savings. The publication recommends best practices for DRaaS implementation, including careful vendor scrutiny, compliance alignment, and hybrid deployment strategies.